2013
DOI: 10.1530/eje-12-0507
|View full text |Cite
|
Sign up to set email alerts
|

Genes that characterize T3-predominant Graves' thyroid tissues

Abstract: Objective: 3,5,3 0 -Triiodothyronine (T 3 )-predominant Graves' disease is characterized by the increasing volume of thyroid goiter resulting in poor prognosis. Although type 1 and type 2 iodothyronine deiodinases (DIO1 and DIO2 respectively) are known to be overexpressed in the thyroid tissues of T 3 -predominant Graves' disease, the pathogenesis of this disease is still unclear. The aim of our study is to identify genes that characterize T 3 -predominant Graves' disease tissue in order to clarify the molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…These patients therefore have a high fT3:fT4 ratio, making it necessary to determine serum free T3 concentrations in patients with long-term undetectable TSH levels, to identify cases with this presentation. These patients have larger thyroid glands and high serum titers of TRAb (21,22,23). They are more likely to be younger and require doses of ATD twice as high as those used in patients with classic GD, over long periods of time, although it remains unclear why the maintenance of high doses is required to overcome the resistance to ATD (21).…”
Section: Monitoring Atd Treatmentmentioning
confidence: 99%
“…These patients therefore have a high fT3:fT4 ratio, making it necessary to determine serum free T3 concentrations in patients with long-term undetectable TSH levels, to identify cases with this presentation. These patients have larger thyroid glands and high serum titers of TRAb (21,22,23). They are more likely to be younger and require doses of ATD twice as high as those used in patients with classic GD, over long periods of time, although it remains unclear why the maintenance of high doses is required to overcome the resistance to ATD (21).…”
Section: Monitoring Atd Treatmentmentioning
confidence: 99%
“…Some recent studies reported an interesting similarity in gene expression between tissues from T 3 predominant Graves' disease and hyperfunctioning adenomas. They overexpress not only iodothyronine deiodinases but also N-cadherin (CDH2) [54,55]. If T 3 predominant Graves' disease is caused by an increased number of fetal thyroid cells, probably prothyrocytes, some clinical features of T 3 -predominant Graves' disease, such as its high prevalence in the young and tendency to form a large goiter, are easily explained.…”
Section: Some Questions Remain To Be Clarified In the Fetal Cell Carcmentioning
confidence: 99%
“…TRAb increases intrathyroidal DIO2 expression and activity, and increased intrathyroidal DIO2 activity may contribute significantly to the relative increase in thyroidal T3 production in GD patients [4]. Two Japanese studies aiming at characterizing the T3-predominant type of GD observed overexpression and increased thyroidal DIO2 activity as well as a high serum fT3/fT4 ratio in patients with T3-predominant GD [29,30]. Thus, DIO2 gene polymorphisms could further modulate these responses.…”
Section: Discussionmentioning
confidence: 99%